Proportional Derivative Active Force Control for “X? Configuration Quadcopter - Tamami, Niam; Pitowarno, Endra; Astawa, I Gede Puja (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2014)
This paper present a control method “x? configuration quadcopter. The control method used PDAFC (Proportional Derivative Active Force Control). PD is used to stabilize quadcopter, and AFC is used to reject uncertainty disturbance (e.g. wind) by estimate disturbance torque value of quadcopter. By adding PD with AFC, better result is obtained, AFC can minimize uncertainty disturbance effect. The sensitivity toward uncertainty disturbance can be set from sensitivity constant to get best performance of disturbance rejection. Stability analysis of PDAFC was evaluated by Lyapunov stability theory.